Developing a Digital Literacy Assessment Framework for 21st-Century Skills in the Indonesian EFL Classroom - Uyunnasirah Hambali; Syahrul Syahrul; Nasir Nasir (AL-ISHLAH: Jurnal Pendidikan, 2026)
The rapid shift toward digital pedagogy has exposed a significant gap in Indonesian English as a Foreign Language (EFL) assessment practices, where traditional testing often fails to capture complex digital literacy. This study aimed to identify teacher needs in digital assessment and construct a validated digital literacy assessment framework that integrates critical thinking, collaboration, and technological proficiency. Employing a Research and Development (RD) design, the study progressed through three phases: needs analysis, prototype design, and expert validation. Data were collected from 45 secondary EFL teachers in South Sulawesi using questionnaires and semi-structured interviews, while three assessment experts evaluated the prototype using validation rubrics. Quantitative data were analyzed using descriptive statistics and Aiken’s V formula, while qualitative data underwent thematic analysis. The needs analysis revealed that current assessments heavily rely on isolated paper-based tests, neglecting students' multimodal skills. In response, a multidimensional framework was developed, encompassing technical competence, digital cognition, and socio-emotional awareness. Expert validation yielded an Aiken’s V coefficient range of 0.82 to 0.94 (mean = 0.88), indicating high content validity, with a practicality rating of 85% from teacher trials. This research concludes that the proposed framework provides a structured pedagogical guideline for educators to transition toward more holistic literacy assessments in the EFL classroom.